Measuring warmth and competence at inter-group, interpersonal and individual levels - Aragonés, Juan I; Poggio, Lucia; Sevillano, Verónica; Pérez-López, Raquel; Sánchez-Bernardos, María Luisa (Revista de Psicología Social, 2017)
Warmth and competence are universal dimensions of social perception that articulate the perception of other individuals and social groups. However, there are no scales that have systematically been used in psychosocial research. The purpose of this study is to construct two scales, one on warmth and another on competence, which could be used at the inter-group, interpersonal and individual levels. To accomplish this, we performed two studies. In Study I (N=578 students and N=540 general population), we tested the scales at the intergroup level (immigrant groups and Spaniards), the interpersonal level (people close to the participants) and the individual level (the participants themselves). In Study 2 (N=184 students), the two scales were tested at an interpersonal level by evaluating 16 public figures. The results of both studies show that both the warmth scale (kind, pleasant, friendly, warm) and the competence scale (competent, effective, skilled, intelligent) achieved a high degree of reliability when reflecting the perception of groups, individuals and oneself. ResumenLa cordialidad y la competencia son dimensiones universales de percepcion social que articulan la percepcion interpersonal y de los grupos sociales. Sin embargo, no existen escalas que hayan sido utilizadas de forma sistematica en la investigacion psicosocial. El objetivo de esta investigacion es construir dos escalas, una de cordialidad y otra de competencia que puedan ser utilizadas en los niveles intergrupal, interpersonal e individual. Para ello se realizan dos estudios. En el Estudio 1 (N = 578 estudiantes y N = 540 poblacion general), se ponen a prueba las escalas en los niveles intergrupal (grupos de inmigrantes y espanoles), interindividual (personas cercanas) e individual (uno mismo). En el Estudio 2 (N = 184 estudiantes) se evaluan 16 personajes publicos. Los resultados de ambos estudios muestran que tanto la escala de cordialidad (amable, agradable, amigable, cordial) como la de competencia (competente, eficaz, habilidoso, inteligente) alcanzan una alta fiabilidad a la hora de responder como se percibe a los grupos, a las personas y a uno mismo.
Keywords: competence; warmth; stereotype content model; social perception; competencia; cordialidad; modelo de contenido de los estereotipos; percepción social; JCR; Scopus